UiTM students academic and curriculum balancing - Othman, Hanis Nurdiana; Abdul Karim, Nur Farahanis; Mohd Zais, Nurul Amyra Khaleda; Kamarul Ariffini, Badrina Batrisyia; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Academic and Curriculum balancing becoming interesting subject to be studied. Academics are really important to our future and life. Without an academic certificate, we cannot pursue our studies or find a better job. On the other hand, curriculum can help students to boost their confidence, release their stress or just to keep on the merits for next semester. Balancing academic and curriculum activities at the same time may be possible for some students with flying colours, but it can have negative impact on their studies for others who are struggling with their academics. The purpose of the investigation is to see if UiTM students can balance between their academic and curriculum activities well. We also want to investigate whether joining a curriculum activities affect their studies and schedule despite the busyness that they need to go through. Based on the finding most students actively follow curriculum activities despite their busy schedule for academics. Various initiatives has been done to divide time between academic and curriculum. Half of the respondents felt that it was quite difficult for them to balance both academic and curriculum as a student, but according to the opinion of the respondents, almost most of them did not experience the disruption of the curriculum to their studies. Nevertheless, based on the survey most of the respondents got average and excellent results. Therefore, it can be concluded that almost all UiTM students can divide their time well for academics and curriculum despite having a busy daily schedule.